Toleransi Berbasis Mashlahah - Jumari Jumari (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2018)
Religion and the nation is a unity can not be separate. Keeping religion means keeping the nation. And vice versa, keeping the nation is sure to keep religion. It can not be said that religion is more important than a nation, or vice versa. Both must be taken care of and cared for properly and wisely, in order to bring peace and harmony into difference. Tolerance is the main attitude in living a diverse life with differences, in order to gain common good. Welfare, security and mutual affection are the main goals. Therefore, if the benefit that is important only by individuals or groups, then should prioritize the benefit of all parties that are general. Thus, the nations welfare that includes all the differences should take precedence over the religions welfare that is personal and not the principle.